The Effect of Bifidobacterium breve and Lactobacillus salivarius on the Gene Expression Involved in Patulin Biosynthesis Produced by Penicillium expansum . - N. Hawar, Sumaiya; S. Karieb, Sahar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Penicillium expansum produced the toxin patulin in pome fruits. To evaluate the molecular mechanism by which the treatment of probiotic bacteria Bifidobacterium breve and Lactobacillus salivarius could modulate patulin production, three genes involved in the biosynthesis of patulin were measured using real time-PCR technique. The result of this study found that the supplementation with B. brave and L. salivarius down-regulate the relative expression of 6-methylsalicylic acid synthase (msas), ATP binding cassette transporter (ABC) and putative cytochrome P450 monooxygenases (P450-1) as well. Although, there is no effect of some strains on this expression. However, these finding suggested that these bacteria decreased patulin production through effect on the genes responsible for its biosynthesis which can be the main mechanism by which patulin reduced in the presence of these bacteria.